Characteristics of tuberculosis contact of children with pulmonary tuberculosis - Magdalena Sidhartani; Retno Murti Laila (Indonesian Pediatric Society, 2006)
Background Children with tuberculosis (TB) are oftenasymptomatic, so that if TB is diagnosed in a child, an adult contactshould be looked for. We realize the importance of TB control bybreaking the chain of transmission, so identification of contact andprompt treatment should be made.Objective To trace contact of children with pulmonary tuberculosis(PTB) and to determine the environmental characteristicsassociated with TB transmission.Methods Prospective, community based descriptive study wasdone in 80 children with newly diagnosed PTB treated atPediatric Pulmonary Ward, Kariadi Hospital, from September2003 to February 2004. Clinical condition, chest x-ray (CXR),acid fast bacilli (AFB) staining of sputum, and environmentalcharacteristics of adults suspected as TB contact wereexamined. Data were analyzed by uni- and bivariate analysisusing SPSS 11.5.Results Eighty adults with suspected TB were enrolled, 90% werehousehold contacts. There were 63 (79%) confirmed TB contactsin rural and urban area. Fathers were predominates (32%)followed by grandparents (26.3%), relatives (18.7%), and mothers(12.5%). There was no significant difference about internal(household) and external (non-household) family contactsbetween rural and urban area (P=1.000). In urban area, hometransmission is more frequent than rural area (P=0.340). In urbanarea, the contacts had a better perception but had no betterattitude toward treatment, although the difference was notsignificant. Behavior was worsen in rural area (P=0.214). Poorbehavior seldom occurred in those who had enough knowledgeof TB, although the difference was not statistically significant(P=0.352). In the urban area, the house of contacts had lowersleeping density (P=0.282), poor ventilation (P=0.306), and higherroom temperature (P=0.683). There were no differences in thelight intensity and humidity.Conclusion There were 79% confirmed TB contacts in rural andurban area with male predominant. There was no significantdifference between household and non-household contacts inrural and urban area. There are different characteristics, such asknowledge, perception, attitude towards treatment, and behaviorassociated with TB transmission between contacts in the ruraland urban area, and between lower, middle, and higher socio-economic level, although the difference is not significant